Performance of missing transverse momentum reconstruction in proton-proton collisions at√s = 7 TeV with atlas - Onofre, A. (2012)
The measurement of missing transverse momentum in the ATLAS detector, described in this paper, makes use of the full event reconstruction and a calibration based on reconstructed physics objects. The performance of the missing transverse momentum reconstruction is evaluated using data collected in pp collisions at a centre-of-mass energy of 7 TeV in 2010. Minimum bias events and events with jets of hadrons are used from data samples corresponding to an integrated luminosity of about 0.3 nb 1 and 600 nb 1 respectively, together with events containing a Z boson decaying to two leptons (electrons or muons) or aW boson decaying to a lepton (electron or muon) and a neutrino, from a data sample corresponding to an integrated luminosity of about 36 pb 1 . An estimate of the systematic uncertainty on the missing transverse momentum scale is presented.